A new parasitoid of the Erythrina Gall Wasp, Quadrastichus erythrinae Kim (Hymenoptera: Eulophidae) - la Salle, John; Ramadan, Mohsen; Kumashiro, Bernarr R. (Zootaxa, 2009)
Aprostocetus exertus La Salle (Hymenoptera: Eulophidae: Tetrastichinae) is described as a parasitoid of the invasive Erythrina Gall Wasp, Quadrastichus erythrinae Kim (Hymenoptera: Eulophidae: Tetrastichinae). The description is based on material originally collected in Tanzania and South Africa. This species is described because of its potential as a biological control agent against the Erythrina Gall Wasp.